Solving Dual Fuzzy Nonlinear Equations via Shamanskii Method - Mohammed Sulaiman, Ibrahim; Mamat, Mustafa; Zamri, Nurnadiah; Liza Ghazali, Puspa (International Journal of Engineering and Technology, 2018)
New ideas on numerical methods for solving fuzzy nonlinear equations have spread quickly across the globe. However, most of the methods available are based on Newtonâ€™s approach whose performance is impaired by either discontinuity or singularity of the Jacobian at the solution point. Also, the study of dual fuzzy nonlinear equations is yet to be explored by many researchers. Thus, in this paper, a numerical method to investigate the solution of dual fuzzy nonlinear equations is proposed. This method reduces the computational cost of Jacobian evaluation at every iteration. The fuzzy coeï¬ƒcients are presented in its parametric form. Numerical results obtained have shown that the proposed method is efficient.Â